Phototropin 1 Mediates High-Intensity Blue Light-Induced Chloroplast Accumulation Response in a Root Phototropism 2-Dependent Manner in Arabidopsis phot2 Mutant Plants - Wang, Jing; Liang, Yu-ping; Zhu, Jin-dong; Wang, Yu-xi; Yang, Meng-ya; Yan, Hong-ru; Lv, Qian-yi; Cheng, Kai; Zhao, Xiang; Zhang, Xiao (Frontiers in Plant Science, 2021)
Phototropins (phot1 and phot2) mediate chloroplast movement to maximize photosynthetic efficiency and prevent photodamage in plants. Phot1 primarily functions in the chloroplast accumulation process, whereas phot2 mediates both chloroplast avoidance and accumulation responses. Phot2-mediated chloroplast avoidance response under high-intensity blue light (HBL) limited the understanding of the function of phot1 in chloroplast accumulation process at the HBL condition. Here, we show that the phot2 mutant exhibits chloroplast accumulation response under HBL, which is defective when the RPT2 gene is mutated in the phot2 background, mimicking the phenotype of the phot1 phot2 double mutant. Further analysis revealed that the expression of RPT2 was induced by HBL and the overexpression of RPT2 can partially enhance the chloroplast accumulation response under HBL. These results confirm that RPT2 also participates in regulating the phot1-mediated chloroplast accumulation response under HBL. By contrast, RPT2 functions redundantly with NCH1 under low-light irradiation. In addition, no chloroplast accumulation response was detected in the phot2 jac1 double mutant under HBL, which has previously been observed in phot2 rpt2 and phot1 phot2 double mutants. Taken together, our results indicate that phot1 mediates the HBL-induced chloroplast accumulation response in an RPT2-dependent manner and is also regulated by JAC1.